107 Early onset liver failure due to mitochondrial DNA depletion: clinical course of four patients. (11th October 2021) - Ramadža, Danijela Petković; Žigman, Tamara; Grizelj, Ruža; Ninković, Dorotea; Omerza, Lana; Aničić, Mirna Natalija; Ćorić, Marijana; Mayr, Johannes A; Feichtinger, René; Wortmann, Saskia; Prokisch, Holger; Fumić, Ksenija; et al.
Abstract : Mitochondrial DNA depletion syndromes (MDS) are a group of autosomal recessive disorders caused by disruption of mtDNA maintenance that results in reduced mtDNA content and disturbed energy production. MDS are genetically and phenotypically heterogeneous. One common phenotype is the hepatocerebral form that manifests in first months of life and causes early death due to liver failure. Liver transplantation (LTx) in not recommended in patients with neurological involvement. Our objective is to raise awareness about the clinical spectrum of early onset liver failure due to MDS. We report clinical course and genotype of four patients with hepatocerebral form of MDS. Patients 1 and 2, daughters of consanguineous Roma parents, presented with liver failure at six and two days of life, respectively. The older sibling had lactic acidosis and progressive liver failure, without clear neurological involvement. Liver histology revealed gigantocellular hepatitis, fibrosis, cholestasis, hemosiderosis and steatosis. Working diagnosis was neonatal hemosiderosis. Despite the treatment, disease progressed to death at 40 days. Younger sibling had similar clinical course and MDS was suspected. Immunohistochemical staining of the deceased sibling's liver showed combined respiratory chain deficiency. Homozygous variant in the DGUOK gene in both patients confirmed the diagnosis. Despite cofactor/antioxidant treatment, patient 2 died at the age of two months. Patient 3 presented with recurrent nonketotic hypoglycemia, cholestasis and hypotonia at the age of two months. Liver disease was slowly progressive, with permanently elevated lactate and alanine. Histology showed gigantocellular hepatitis, fibrosis, cholestasis, hemosiderosis, polymorphous mitochondria and microvesicular steatosis. MDS was suspected, but immunohistochemical staining was uninformative. Due to end-stage liver disease, LTx was performed at the age of six months. Patient died in early postoperative period. Whole exome sequencing (WES) revealed biallelic mutations in the MPV17 gene. Patient 4 had intrauterine growth retardation, severe hypotonia and developmental delay since birth. Acute liver failure, presenting with ketotic hypoglycemia, lactic acidosis, hepatomegaly and coagulopathy, occurred at the age of four months. The individual additionally developed nystagmus. Brain MRI was normal. Liver biopsy showed steatosis and abnormal mitochondria. Immunohistochemistry and clearly decreased mtDNA copy number per nuclear genome in liver pointed to MDS. The disease progressed rapidly and patient died three weeks after admission. WES revealed two biallelic mutations in the POLG gene. Revealing genetic basis of liver failure due to MDS, with WGS as an important option, is pre-requisite to decision on LTx. It is also essential for genetic counseling and prenatal diagnosis in future pregnancies.